Development of Textbooks for Elementary School Curriculum Study and Development Course - Sa’dun Akbar; Oktarianto, M. Luthfi; Erif Ahdhianto; Dinik Hanisvana; Rifqi Al Farizza (EDUTEC : Journal of Education And Technology, 2024)
This study aims to develop a textbook for the Elementary School Teacher Education program, specifically targeting 5th-semester students. The textbook is designed to align with the current syllabus of the Elementary School Curriculum Study and Development course, focusing on enhancing students' conceptual understanding of the subject. To ensure the textbook’s effectiveness in promoting learning, the ADDIE model—comprising Analysis, Design, Development, Implementation, and Evaluation—was used as the research framework. Data was collected using a semi-open questionnaire for validation purposes. Expert validation showed strong qualification scores across three key areas: content and material (87.50%), presentation (89.06%), and language (87.50%). In addition, small group trials conducted with 30 students yielded an average acceptance rate of 87.00%, confirming that the textbook is well-received and suitable for use in the course. This study contributes to the development of curriculum materials that are aligned with the evolving educational paradigm and enhances the quality of teaching in elementary education.